2020
DOI: 10.1186/s12891-020-3115-x
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior debridement, bone grafting fusion, and mono-segment vs. short-segment fixation for single-segment lumbar spinal tuberculosis: minimum 5-year follow-up outcomes

Abstract: Background: To compare the clinical and radiological outcomes between posterior mono-segment and shortsegment fixation combined with one-stage posterior debridement and bone grafting fusion in treating singlesegment lumbar spinal tuberculosis (LSTB). Methods: Sixty-two patients with single-segment LSTB treated by a posterior-only approach were divided into two groups: short-segment fixation (Group A, n = 32) and mono-segment fixation (Group B, n = 30). The clinical and radiographic outcomes were analyzed and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This pathological process results in stronger holding forces for pedicle screws in the involved vertebrae, compared with fracture [ 24 ]. Liu et al [ 25 ] compared the results of mono-segment fixation versus short-segment fixation for the treatment of single-segment lumbar spinal TB and found that mono-segment fixation was more suitable since the normal motion was preserved. Xu et al [ 26 ] reported that single-segment fixation and bone fusion was effective in maintaining the stability of the spine and retaining normal motion units.…”
Section: Discussionmentioning
confidence: 99%
“…This pathological process results in stronger holding forces for pedicle screws in the involved vertebrae, compared with fracture [ 24 ]. Liu et al [ 25 ] compared the results of mono-segment fixation versus short-segment fixation for the treatment of single-segment lumbar spinal TB and found that mono-segment fixation was more suitable since the normal motion was preserved. Xu et al [ 26 ] reported that single-segment fixation and bone fusion was effective in maintaining the stability of the spine and retaining normal motion units.…”
Section: Discussionmentioning
confidence: 99%
“…This pathological process results in stronger holding forces for pedicle screws in the involved vertebrae compared with fracture [24]. Liu et al [25] compared the results of mono-segment xation versus short-segment xation for the treatment of single-segment lumbar spinal TB and found that mono-segment xation was more suitable since the normal motion was preserved. Xu et al [26] reported that single-segment xation and bone fusion was effective in maintaining the stability of the spine and retaining normal motion units.…”
Section: Discussionmentioning
confidence: 99%
“…They also evaluated the single posterior debridement, interbody fusion and fixation technique for lumbar CMSTB. Lumbar constitutes the lower part of the spine and bears the maximum weight, and hence, it is often associated with internal fixation failure [26]. Currently, there is no literature relevant to lumbar CMSTB.…”
Section: Discussionmentioning
confidence: 99%